The cannabinoid receptor type 1 is essential for mesenchymal stem cell survival and differentiation: implications for bone health. - Campbell, Veronica (My University, 2013)
Significant loss of bone due to trauma, underlying metabolic disease, or lack of repair due to old age surpasses the body’s endogenous bone repair mechanisms. Mesenchymal stem cells (MSCs) are adult stem cells which may represent an ideal cell type for use in cell-based tissue engineered bone regeneration strategies. The body’s endocannabinoid system has been identified as a central regulator of bone metabolism. The aim of the study was to elucidate the role of the cannabinoid receptor type 1 in the differentiation and survival of MSCs. We show that the cannabinoid receptor type 1 has a prosurvival function during acute cell stress. Additionally, we show that the phytocannabinoid, -Tetrahydrocannabinol, has a negative impact on MSC survival and osteogenesis. Overall, these results show the potential for the modulation of the cannabinoid system in cell-based tissue engineered bone regeneration strategies whilst highlighting cannabis use as a potential cause for concern in the management of orthopaedic patients.
PUBLISHED
Keywords: Cannabinoid Receptor Type 1; Next Generation Medical Devices